The Role of Village Heads in Aceh Jaya in Combating Poverty Through the Utilization of Village Funds - Jon Paisal, Sukri, Arwin Jon Paisal (Empower : Jurnal Pengembangan Masyarakat Islam, 2024)
The problem of poverty in Indonesia is a national problem that requires long-term solutions. As part of the government's efforts, village heads are authorized to manage village funds from the APBN with the aim of reducing poverty in villages. However, there are still many poor people, including in Aceh Province. In 2021, the number of poor people in Aceh will reach 850,260 people, with the poverty percentage increasing by 0.25 points to 15.53 percent, or an increase of 16,020 people according to data from the Central Statistics Agency (BPS). In Aceh Jaya Regency, the percentage of poor people reached 13.23% even though this area received village funds for each village. This study aims to determine the role of village heads in overcoming poverty through the use of village funds. The research method uses a field approach with data collection techniques through interviews, documentation, and observation. The results of the study show that before realizing the budget, the village head prepares a village development program plan with the assistance team and community leaders. After the APBDes is approved, activities are carried out according to the plan agreed upon in the village meeting. In the implementation stage, the village head forms an Activity Implementation Team (TPK) to work on projects such as building roads and bridges, and decent housing. In the field of community economic empowerment, the village head in Aceh Jaya provides business capital and direct money to underprivileged residents. In addition, economic programs include clean water management and BUMDes businesses such as palm oil trading, where the profits are given to the poor, such as in Alu Pit village, Panga District. After the implementation is realized, the village head makes an accountability report to the local government. Then conduct an annual performance evaluation to assess the effectiveness and efficiency of the use of village funds, the results are used as a basis for improving and adjusting the activity plan for the following year